Analysis of the Effectiveness of Using Mobile Banking Services in Increasing Customer Satisfaction of Bank Syariah Indonesia - Putri, Yuliana; Nasution, Juliana; Yanti, Nursantri (Jurnal Iqtisaduna, 2025)
This study aims to analyze the effectiveness and use of mobile banking services in increasing customer interest and satisfaction at Bank Syariah Indonesia (BSI), based in BSI KC Tomang Elok, Medan. With the rapid development of technology, mobile banking services have become one of the main innovations in the banking industry that has the potential to significantly affect customer experience. This study uses a qualitative method with descriptive analysis techniques where data is collected and found through observation, interviews, documentation, websites and books to obtain information and evidence in the research process. The results of the study indicate that effective use of mobile banking can increase customer satisfaction and interest in Islamic banking services. Factors such as ease of access, transaction speed, and application features play an important role in influencing customer perceptions. These findings are expected to provide insight for BSI management in improving the quality of mobile banking services and marketing strategies to attract more customers.